UPAYA PENINGKATAN KOMPETENSI PROFESIONAL GURU SEKOLAH ADIWIYATA DALAM PELAKSANAAN ECOLOGICAL CITIZENSHIP (STUDI DI SMA NEGERI 4 SURAKARTA) - Nugroho, Intan Ari; ., Triyanto; Rejekiningsih, Triana (PKn Progresif, 2017)
ABSTRACTThe purpose of this study were: 1) Determine the application Adiwiyata School at SMAN 4 Surakarta. 2) Knowing improvement of the professional competence of school teachers in the implementation of Ecological Citizenship in SMA Negeri 4 Surakarta. 3) Know the issues and solutions faced by teachers in improving the professional competence of school teachers in the implementation of Ecological Citizenship in SMA Negeri 4 Surakarta.This study is the descriptive qualitative research. The research data was obtained from the informants, places, and the documents. Purposive sampling was used for the sampling technique. Interviews, observations, and the documents analysis were used to collect the data. The data validity used the data and method triangulations. To analyze the data, an interactive analysis model was used. Based on the research results, it can be concluded that: 1) Implementation Adiwiyata School in SMA Negeri 4 Surakarta can be concluded that the application of the policy pursued in the school had implemented a change in the vision and mission of the school is the protection and management of environment, policy insertion environmental insight into subjects, and policies that contain rules or order to safeguard the environment. 2) Development of professionalism of teachers on an ongoing basis can be done through activities such as: training, courses, training, upgrading and other forms of education and training. Regarding the utilization of information and communication technology, teachers have a high willingness to implement ICT in the learning process, it can be seen from the use of media-based learning effective video used in learning environmentally sound, while also using the group WhatsApp as a medium of learning is flexible, and the use of new learning media is Quipper School. 3) The problem of teachers in improving the professional competence of school teachers in the implementation of the Ecological Adiwiyata citizenship are: management time in learning activities, especially with the ability of students to understand the material provided and the insertion of environmental education with the subjects of teaching. While the solution of teachers in dealing with the problems facing the management of time is not good that the teachers sharing experience with other teachers when it got into trouble, it gives students the understanding to explain the material that has not been understood by other students and provide additional value to students who able to explain the material well and clearly, and to maximize the practical activities- related to managing the waste that is around to make compost from waste paper crafts and others, as well as inserting understanding the value of protecting the environment well. Keywords: Teacher, Professional Competence, Adiwiyata School, Ecological Citizenship